Reducing Actuators in Soft Continuum Robots and Manipulators - Mohamed Shoani, Mohamed Shoani; Mohamed Najib Ribuan, Mohamed Najib Ribuan; Ahmad Athif Mohd Faudzi, Ahmad Athif Mohd Faudzi; Shahrol Mohamaddan, Shahrol Mohamaddan (Mdpi, 2023)
Soft continuum robots and manipulators (SCRaMs) are elongated structures that can be used in many applications, such as exploration, inspection, and minimally invasive surgery. Multi‐ segment SCRaMs employ numerous actuators to perform their tasks. The large number of actuators increases the cost and complexity of a SCRaM and reduces its reliability. In this paper, a methodol‐ ogy is presented to reduce the number of actuators employed by SCRaMs while maintaining their volumetric workspace. The method presents a new design approach involving one rotary and two linear actuators, providing three degrees of freedom (DOF) and a volumetric workspace. The result of applying the transformation is a 50–86% reduction in the total number of actuators typically em‐ ployed by multi‐segment SCRaMs. The application of this methodology reduces the cost and com‐ plexity of conventional multi‐segment SCRaMs while improving their efficiency and reliability